PENGARUH REFRIGERAN CAMPURAN HALOKARBON DAN HIDROKARBON TERHADAP TEMPERATUR EVAPORATOR - Khambali; Listiyono (Jurnal Teknik Ilmu dan Aplikasi, 2020)
Hydrocarbon refrigerant is a type of environmentally friendly refrigerant but it has disadvantages compared to halocarbon refrigerant which is flammable. The purpose of mixing hydrocarbon refrigerants with halocarbons in the study was to determine the effect of the percentage of the refrigerant mixture on the temperature of the evaporator and reduce its flameability. The percentage of the mass of the mixed refrigerant mixture that is loaded and time is used as the independent variable, the evaporator temperature as the dependent variable. So the relationship between time and evaporator temperature will be known for each percentage of the mass of the refrigerant mixture. Hasil penelitian menunjukkan bahwa komposisi campuran massa refrigeran hidrokarbon dengan halocarbon berpengaruh terhadap laju perubahan temperatur evaporator. Persentase hidrokarbon dalam campuaran refrigeran HC-HCFC semakin besar dapat meningkatkan laju penurunan temperatur pada evaporator. Semakin besar persentase hidrokarbon dapat menghasilkan pencapaian temperatur semakin rendah pada evaporator.